Gravity on crystallization of lysozyme: slower or faster? - Yang,H; Huang,L; Zhang,F; Karde,V; Yang,Z; Heng,JYY (Crystal Growth and Design, 2019)
With the increase in applications of protein-based medicines approved and developed, downstream manufacturing of biopharmaceuticals has challenges of finding cost-effective and reliable routes. Biocrystallization and centrifugation have both been used to isolate and purify macromolecules, such as therapeutic protein and other functional proteins. However, the centrifugation cannot perfectly separate biomolecules, and the biocrystallization mainly focuses on structure determination on a scale of microliters or below. In this work, protein crystallization of lysozyme, with a concentration of 35–45 mg/mL, and sodium chloride, with a concentration of 45–55 mg/mL in the solution, on a scale of milliliters was performed under centrifugation. Different gravity levels of 1–20000g and centrifugation durations have been investigated during the nucleation and crystal growth process. There were no obvious influences of low gravity (<100g) and short duration (<5 min) of centrifugation on the crystallization process: i.e., on the changes in concentrations. With continuous centrifugation (>30 min), high gravity (>1000g) hindered the nucleation, i.e., it reduced the drop in concentration at the nucleation stage; however, it accelerated the crystal growth process, i.e. enhanced a drop in concentration at the crystal growth stage.